L’imagerie touarègue entre littérature savante et littérature populaire - Paul Pandolfi (L’Année du Maghreb)
To this day, a number of clichés continue to hinder our understanding of the Tuareg society. With different degrees and some adjustments, such clichés usually emerge in travel literature, media, movies, advertising, and sometimes in academic publications. This article is primarily based on the analysis of the stereotypical representation of Tuaregs in the “scholarly” literature of the colonial era, with particular references to two authors who have been instrumental in its development: Henri Duveyrier and Emile-Felix Gautier. The article then examines a number of colonial novels that were directly inspired by scholarly literature. In these clichés, the Tuareg appears as an “other”, but an “other” close enough to project a rather positive image, and his relative proximity makes all the more obvious the irremediable otherness of his neighbors, who in turn are given negative stereotypes.